336 TEMPORAL CONNECTION BETWEEN HOME MONITORING TRENDS OF THORACIC IMPEDANCE AND SUSTAINED VENTRICULAR ARRHYTHMIAS. (15th December 2022) - Rodio, Giovanna; Iacopino, Saverio; Pisanò, Ennio C; Calvi, Valeria; Rovaris, Giovanni; Marini, Massimiliano; Giammaria, Massimo; Caravati, Fabrizio; Maglia, Giampiero; Maines, Massimiliano; Orsida, Daniela; Santamaria, Matteo; et al.
Abstract: Introduction: Implantable cardioverter defibrillators (ICDs) provide daily values of thoracic impedance (TI) that are inversely correlated with fluid accumulation in the lungs. Since sustained ventricular arrhythmias (SVA) are known to have a short-term relationship with heart failure exacerbations, our objective was to assess TI trends temporally related to SVA episodes. Methods: This study analyzed data daily transmitted from patients with ICD or cardiac resynchronization therapy defibrillator (CRT-D) of the nationwide Home Monitoring Expert Alliance network. Device-detected SVAs were adjudicated for appropriateness. Patients were randomly split into a derivation and validation cohort. To identify the most significant TI trend (TI-index), several numerical TI transformations were tested in a cross-sectional analysis of the derivation cohort modelling the odds of first SVA with univariate logistic regressions. In the same cohort, the threshold of the selected transformation was identified to maximize the projected specificity. The relative risk of SVA for TI-index above threshold was estimated in the validation cohort by applying Cox proportional hazard models stratified by individual patients to 60-day duration windows. Analyses were performed separately in the ICD and CRT-D groups. Results: The study cohort included 2, 384 patients with 69 years of age (interquartile range: 60, 77); 19% were women, 42% had coronary artery disease, and 43% had a CRT-D. After a median follow-up of 2.0 (1.0, 3.4) years, there were 3, 298 appropriate SVA episodes in 727 patients (30%). The derived IT-index consisted of the percentage of 6-day intervals of the rolling average of TI values showing monotone decrease in the last 82 days. The increase in the risk of SVA was 3% (p<0.0001) per unit of percentage. The threshold of 60% of intervals with monotone decrease was associated with 99.9% projected specificity and 70.3% accuracy. In the validation cohort, the TI-Index was associated with a 42% increased risk of SVA episodes in the ICD group (hazard ratio [HR] 1.42, 95% confidence interval [CI] 1.05-1.92, p=0.023). The TI-index exceeded the 60% threshold before the episode in 38% of the detected episodes. The association was not significant in the CRT-D group (HR 0.96, 95% CI 0.62-1.47, p=0.84). Conclusions: In our analysis of remote monitoring data, a specific monotonic decreasing trend of TI was temporally associated with SVA in patients with ICD. Careful monitoring of TI can identify a period of susceptibility to ventricular arrhythmias that deserves more intensive attention.